Picturing thermal niches and biomass of hydrothermal vent species. (March 2017) - Husson, Bérengère; Sarradin, Pierre-Marie; Zeppilli, Daniela; Sarrazin, Jozée
Abstract: In community ecology, niche analysis is a classic tool for investigating species׳ distribution and dynamics. Components of a species׳ niche include biotic and abiotic factors. In the hydrothermal vent ecosystem, although composition and temporal variation have been investigated since these deep-sea habitats were discovered nearly 40 years ago, the roles and the factors behind the success of the dominant species of these ecosystems have yet to be fully elucidated. In the Lucky Strike vent field on the Mid-Atlantic Ridge (MAR), the dominant species is the mussel Bathymodiolus azoricus. Data on this species and its associated community were collected during four oceanographic cruises on the Eiffel Tower edifice and integrated in a novel statistical framework for niche analysis. We assessed the thermal range, density, biomass and niche similarities of B. azoricus and its associated fauna. Habitat similarities grouped mussels into three size categories: mussels with lengths ranging from 0.5 to 1.5 cm, from 1.5 to 6 cm, and mussels longer than 6 cm. These size categories were consistent with those found in previous studies based on video imagery. The three size categories featured different associated fauna. The thermal range of mussels was shown to change with organism size, with intermediate sizes having a broader thermal niche than small or large mussels. Temperature maxima seem to drive their distribution along the mixing gradient between warm hydrothermal fluids and cold seawater. B. azoricus constitutes nearly 90% of the biomass (in g dry weight /m 2 ) of the ecosystem. Mean individual weights were calculated for 39 of the 79 known taxa on Eiffel Tower and thermal ranges were obtained for all the inventoried species of this edifice. The analysis showed that temperature is a suitable variable to describe density variations among samples for 71 taxa. However, thermal conditions do not suffice to explain biomass variability. Our results provide valuable insights into mussel ecology, biotic interactions and the role of B. azoricus in the community.